The Legal Status of the Psychiatrist in the Criminal Justice System: A Comparative Study - Al-Makhzoumi وليد; MUSTAFA أحمد (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
This research aims to study and define the legal status of the psychiatrist in the criminal justice system and how it can either strengthen the foundations of this system or lead to its collapse and the squandering of its values. It examines the legal regulation of the role of the psychiatrist in the current mental health law, adopting a descriptive approach reinforced by theoretical analysis, both in Iraqi law and in comparative law in some Arab countries. It then begins by explaining what is meant by a psychiatrist and the conditions for the legitimacy of practicing this function, the legal basis for the psychiatrist's intervention in the criminal justice system, and defining his role in accordance with this criminal justice system as defined by Iraqi and comparative legislators. It then outlines the crimes that a psychiatrist could potentially commit in the course of practicing their profession, which would obstruct the criminal justice system from performing the task intended by the legislator.